The Course Management System Workflow-Oriented to Control Admission and Academic Process - Usman Rizal; Yuthsi Aprilinda (Bandar Lampung University (UBL), 2012)
Course Management System (CMS) is a secure web based management system which is specifically designed for controlling studentâs admission and academic process. This system is designed to detail the activities streamline of studentâs admission and academic process, such as how and when the application should be started, and how to coordinate the resources amongst other stakeholders. This system is designed based on the ISO 9001:2008 Management Quality System General Requirement Clause 4.1(b) and Clause 4.1(c).